Inconsistency in community structure and ecological quality between platform and cliff coralligenous assemblages. (March 2022) - Piazzi, Luigi; Ferrigno, Federica; Guala, Ivan; Cinti, Maria Francesca; Conforti, Alessandro; De Falco, Giovanni; De Luca, Mario; Grech, Daniele; La Manna, Gabriella; Pascucci, Vincenzo; Pansini, Arianna; Pinna, Federico; et al.
Highlights: Structure and ecological quality of coralligenous cliff and platform were assessed. Six geographic areas around Sardinia were considered. The ecological quality was assessed by ESCA and CBQI indices. Variability in assemblages structure changed between the two morphologies. Spatial patterns in the ecological quality differed between platform and cliff. Abstract: Coralligenous reefs are the main biogenic constructions of the Mediterranean Sea and they are considered indicators of the ecological quality of coastal systems and of "seafloor integrity" by the Marine Strategy Framework Directive. The two main coralligenous morphologies are the cliffs and platforms, the former developing in shallow waters (about 20–50 m) on vertical/subvertical rocky substrate and the latter built over horizontal substrates below 50 m depth also on detritic bottoms. The present study aims at assessing whether patterns of spatial variability and ecological quality of the coralligenous cliff assemblages reflect those of platform assemblages. At this aim, six geographic areas around Sardinia (western Mediterranean, Italy) were considered and, within each area, the structure of both the coralligenous cliffs and platforms was investigated by SCUBA and ROV methods, and their ecological quality was assessed by ESCA and CBQI indices, respectively. Overall, 20 morphological groups (seven macroalgae and thirteen invertebrates) were found but differences in community structure were evident both spatially and between systems, platforms vs cliffs. In fact, spatial variability in assemblages structure changed between the two morphologies across the areas. Moreover, a different spatial pattern in the ecological quality was found between platform and cliff assemblages. The results of the present study corroborate the individual peculiarity of coralligenous platforms and cliffs, highlighting the importance of the concurrent assessment of both systems in monitoring programs..